RELATIONSHIP BETWEEN NIGHT-TIME DYSPNEA EPISODES AND HEART RATE VARIABILITY - Szabó, Krisztina; Balogh, László; Ihász, Ferenc (Stadium - Hungarian Journal of Sport Sciences, 2020)
Purpose: We wanted to assess the values of expected night-time and day-time variability of the heart rate, in the presence of dyspnea episodes during night-time, recorded by a Holter monitor.Objective: Our aim was to investigate whether nocturnal breathing disorders affect the HRV indexes. Methods: 40 patients participated in our survey. 20 of them experienced episodes of night-time breathing difficulty, and the control group consisted of 20 participants in whose case there were no episodes of night-time breathing difficulty. We were examining the domains of time and frequency of heart rate variability, using day-time and night-time values recorded by a 24-hour Schiller Medilog Holter monitor. We evaluated the distribution of the parameters with a continuous codomain, their typical distribution and expected values on histograms, and summarized them in a table. For the examination of the difference in averages the Two-Sample T- Test was used, where p